2010
DOI: 10.1007/s00442-010-1732-z
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of climate change on the wintering distribution of an endangered migratory bird

Abstract: There is now ample evidence of the effects of anthropogenic climate change on the distribution and abundance of species. The black-faced spoonbill (Platalea minor) is an endangered migratory species and endemic to East Asia. Using a maximum entropy approach, we predicted the potential wintering distribution for spoonbills and modeled the effects of future climate change. Elevation, human influence index and precipitation during the coldest quarter contributed most to model development. Five regions, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 59 publications
3
54
0
Order By: Relevance
“…Our study indicated that increasing the carrying capacity (K) in Przewalski's gazelle can slow down the trend of population decline (Appendix D). As suggested by both observed and predicted effects of climate change on biodiversity (Hu et al, 2010a;Root et al, 2003), species' responses to a changing environment may be influenced by changes in suitable habitat, population processes, and interactions between different species as well as between demographic and landscape dynamics (Keith et al, 2008;. As the climate of the Qinghai lake region is becoming warmer and drier (Ma and Jiang, 2006), the effects of climate change on Przewalski's gazelle would increase with the time horizon as determined by measuring the shift in availability of suitable habitat (Hu and Jiang, 2011).…”
Section: Sensitivity Analysismentioning
confidence: 58%
“…Our study indicated that increasing the carrying capacity (K) in Przewalski's gazelle can slow down the trend of population decline (Appendix D). As suggested by both observed and predicted effects of climate change on biodiversity (Hu et al, 2010a;Root et al, 2003), species' responses to a changing environment may be influenced by changes in suitable habitat, population processes, and interactions between different species as well as between demographic and landscape dynamics (Keith et al, 2008;. As the climate of the Qinghai lake region is becoming warmer and drier (Ma and Jiang, 2006), the effects of climate change on Przewalski's gazelle would increase with the time horizon as determined by measuring the shift in availability of suitable habitat (Hu and Jiang, 2011).…”
Section: Sensitivity Analysismentioning
confidence: 58%
“…We also quantify the environmental niche differentiation between gazelles across the whole geographic range in Procapra. The results in this study will help with regional or national conservation and management plans (e.g., Hu et al 2010a;Hu and Jiang 2010) and incite further research of niche evolution for Procapra.…”
Section: Introductionmentioning
confidence: 84%
“…The use of species distribution models (SDMs) combined with geographic information systems has led to a renaissance in addressing questions related to ecology, biogeography, evolutionary process, and species conservation (Guisan and Thuiller 2005;Hu et al 2010a;Lawler et al 2009;Peterson et al 1999;Warren et al 2008). SDMs are typically used for addressing ecological niche requirements of species and identifying potential areas with a high probability of presence for the focal species based on the environment attributes (Guisan and Thuiller 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing proportion of spoonbills have started wintering in Europe over the last few decades (unpublished data). Moreover, climate change has been predicted to cause a northward shift of the wintering distribution of the black-faced spoonbill, Platalea minor (Hu et al 2010). This suggests that wintering sites in the northern part of the wintering range may have become more suitable over time.…”
Section: Discussionmentioning
confidence: 99%